2020
DOI: 10.1101/2020.01.29.924886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATG8-interacting (ATI) 1 and 2 define a plant starvation-induced ER-phagy pathway and serve as MSBP1 (MAPR5) cargo-receptors

Abstract: ER-phagy, the selective autophagy of endoplasmic reticulum (ER) components, is known to operate in eukaryotes from yeast and unicellular algae to animals and plants. Thus far, only ER-stress derived ER-phagy was reported and analyzed in plants. In this study we characterize an ER-phagy pathway in Arabidopsis thaliana that is triggered by dark-induced starvation and not by ER-stress. This pathway is defined by the previously reported ATG8interacting proteins, ATI1 and ATI2 and is regulated by the TOR signaling … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…They are type II transmembrane proteins of 256 and 266 residues, respectively ( FIGURE 10 ), which were shown to interact with Atg8/LC3 proteins by yeast split Ub assay and Atg8f and Atg8h as baits ( 294 , 295 ). Consistently, they display a LIR motif within their long cytosolic NH 2 -terminal intrinsically disordered domain ( 258 , 296 ) ( FIGURE 10 ). Dark-induced carbon starvation triggers ATI1 and ATI2 association with Atg8f and segregation in spherical ER bodies, which are eventually transported into the vacuole for clearance via direct ER-to-vacuole trafficking ( 294 , 297 , 298 ).…”
Section: Autophagy Of the Er: Er-phagymentioning
confidence: 78%
See 1 more Smart Citation
“…They are type II transmembrane proteins of 256 and 266 residues, respectively ( FIGURE 10 ), which were shown to interact with Atg8/LC3 proteins by yeast split Ub assay and Atg8f and Atg8h as baits ( 294 , 295 ). Consistently, they display a LIR motif within their long cytosolic NH 2 -terminal intrinsically disordered domain ( 258 , 296 ) ( FIGURE 10 ). Dark-induced carbon starvation triggers ATI1 and ATI2 association with Atg8f and segregation in spherical ER bodies, which are eventually transported into the vacuole for clearance via direct ER-to-vacuole trafficking ( 294 , 297 , 298 ).…”
Section: Autophagy Of the Er: Er-phagymentioning
confidence: 78%
“…These ER bodies, which colocalize with both ATI1 and ATI2, accumulate in the vacuole when cells are exposed to concanamycin A. This antibiotic raises the vacuolar pH by inhibiting the vacuolar ATPase inactivating the proteolytic enzymes ( 299 ) and proves the involvement of these two receptors in ER-phagy ( 296 ). Dark-induced ER-phagy also regulates the turnover of the ER-localized membrane steroid binding protein 1 ( 300 ).…”
Section: Autophagy Of the Er: Er-phagymentioning
confidence: 99%
“…ATI1 also localizes to the ER and interacts with ER-localized ARGONAUTE1 (AGO1), suggesting a role as a selective cargo receptor for AGO1 [ 51 ]. Recently, Wu et al demonstrated that ATI proteins participate in dark-induced ER-phagy, independent of ER stress [ 52 ]. Their results also suggested that this dark-induced ER-phagy requires the repression of TOR, a conserved kinase that negatively regulates autophagy in response to nutrients.…”
Section: Er-phagy Receptors In Plants and Their Functionsmentioning
confidence: 99%
“…Plant ER-phagy has primarily been studied during ER stress, in which chemical agents, heat stress or pathogens lead to the accumulation of unfolded or misfolded proteins. Interestingly, in a recent study, dark treatment was found to trigger ER-phagy in a process dependent on the ATI proteins, but independent of ER stress [ 52 ]. In another case, local phosphate deficiency was able to activate ER-stress dependent autophagy.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%